The Effectiveness of Mediation in Resolving Land Disputes at the National Land Agency of Banyumas Distric - Yanuar Dwi Yanto (Proceedings Series on Social Sciences & Humanities, 2023)
Land disputes are a complex and frequent problem in Indonesia. This research aims to evaluate the effectiveness of mediation in land dispute resolution with a focus on the legal framework governing land dispute mediation. The research method used is normative juridical which focuses on analysing legislation and legal materials, as well as policies and procedures applied in conducting land dispute mediation. The results of the research examine how effective mediation is in the land dispute resolution process and provide a deeper understanding of the legal framework and policies governing land dispute mediation. The Law of the Republic of Indonesia No. 30 Year 1999 on Arbitration and Alternative Dispute Resolution provides the legal basis for the use of mediation as a method of resolving land disputes. The National Land Agency is one of the bodies that has the authority to conduct mediation, especially land disputes, so its effectiveness is needed so that mediation runs smoothly according to the procedures that have been regulated and can be resolved without going through a trial process that is costly and time consuming. However, there are still several challenges in the implementation of land dispute mediation, namely inadequate public understanding and lack of awareness of the benefits of mediation, as well as the lack of quality trained mediators. Therefore, more intensive efforts are needed in socialisation and education on land dispute mediation to the community and capacity building of mediators involved in the mediation process.